Relationship of linear type traits with production and reproduction performance in Murrah buffaloes - DAHIYA, S P; KUMAR, MANOJ; DHILLOD, SANDEEP (The Indian Journal of Animal Sciences, 2020)
Murrah is the world famous milch breed of buffaloes. The aim of present study was to study the variability in body conformation traits as well as to assess the relationship of body conformation traits with production and reproduction performance of Murrah buffaloes. The measurements on 81 lactating Murrah buffaloes maintained at Buffalo Farm, Lala Lajpat Rai University of Veterinary and Animal Sciences, Hisar were recorded for 11 morphometric traits, viz. top wedge angle, rump slope, rump width, hip bone distance, navel flap length, brisket distance, height at wither, body length, skin thickness at neck region, skin thickness at chest region and skin thickness at flank region and their means along with standard errors were 46.9±0.5 degree, 13.0±0.6 degree, 17.7±0.3 cm, 47.0±0.4 cm, 1.8±0.1 cm, 24.3±0.5 cm, 138.5±0.4 cm, 148.9±0.8 cm, 6.7±0.1 cm, 9.0±0.2 cm and 11.3±0.2 cm, respectively. Additionally, four performance traits namely first lactation milk yield, age at first calving, service period and calving interval were also recorded and their means were found to be 2934.4±95.9 kg, 42.8±0.6 months, 141.7±9.9 days and 446.6±12 days, respectively. The top wedge angularity and hip bone distance had significant positive correlations with first lactation milk yield (0.42 and 0.52 respectively). Highest (0.86) and significant correlation was observed between service period and calving interval. The results suggest that Murrah buffaloes with higher top wedge angularity and wider hip bone distance are better in milk production and these traits can be used for selection of high producing buffaloes in the absence of milk records under field conditions.